Sputter deposited silver film as an alternative tool for Raman signal enhancement in plasma-activated water - Azevedo Neto, Nilton F.; Marques, Samuel A.; Miranda, Felipe S. [UNESP]; Moreira Junior, Pedro W.P.; Pereira, Andre L.J.; Constantino, Carlos J.L. [UNESP]; da Silva, José H. Dias [UNESP]; Pessoa, Rodrigo S. (Elsevier, 2025)
Plasma-activated water (PAW), generated by non-thermal plasma, has shown great potential in various applications, including bacterial inactivation, agriculture, and disinfection, primarily attributed to the presence of reactive oxygen and nitrogen species (RONS). Traditional characterization methods for RONS in PAW often encounter limitations in sensitivity and specificity, particularly at low concentrations. In this study, we investigated the application of surface-enhanced Raman spectroscopy (SERS) for the characterization of PAW. A SERS substrate was prepared by sputter-depositing a silver (Ag) film onto a cover glass. The structural, topographic, and optical properties of the film were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), and reflectance spectroscopy. Utilizing the Ag film substrates, we observed a substantial enhancement in the Raman signals of deionized water compared to measurements on glass substrates, achieving an analytical enhancement factor (AEF) of approximately 30 for the O–H stretching band. The characterization of PAW using the SERS substrate enabled the acquisition of well-defined Raman spectra and facilitated the detection of nitrate ions (NO₃⁻) in PAW generated by a dielectric barrier discharge reactor. The results obtained from the PAW Raman spectra were further supported by changes in physicochemical properties, such as decreased pH and increased conductivity, as well as UV-Vis spectroscopy results. These findings demonstrate that sputter-deposited Ag films can serve as a valuable methodological tool for the characterization of PAW using Raman spectroscopy.
Keywords: Plasma-activated water; Reactive oxygen and nitrogen species; Silver film; Sputtering; Surface-enhanced Raman spectroscopy